2010
DOI: 10.1603/ec10027
|View full text |Cite
|
Sign up to set email alerts
|

Association of “<I>Candidatus</I> Liberibacter solanacearum” With the Psyllid, <I>Trioza apicalis</I> (Hemiptera: Triozidae) in Europe

Abstract: The psyllid Trioza apicalis Förster (Hemiptera: Triozidae) is a serious pest of carrots, Daucus carota L., in Europe. Carrots exhibiting symptoms of psyllid damage were observed in commercial fields in southern Finland in 2008. Symptoms in affected plants included leaf curling, yellow and purple discoloration of leaves, stunted growth of shoots and roots, and proliferation of secondary roots. Mechanisms by which T. apicalis induces symptoms in plants are not understood, and no plant pathogens have yet been ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 51 publications
1
103
1
5
Order By: Relevance
“…The bacterium was detected in eggs, in different nymph instars and in adults of B. cockerelli (Hansen et al, 2008) and in field-collected and laboratory-reared T. apicalis by conventional PCR (Munyaneza et al, 2010). The bacterium was also detected in B. trigonica, B. tremblayi, B. nigricornis and Bactericera sp.…”
Section: Introductionmentioning
confidence: 91%
“…The bacterium was detected in eggs, in different nymph instars and in adults of B. cockerelli (Hansen et al, 2008) and in field-collected and laboratory-reared T. apicalis by conventional PCR (Munyaneza et al, 2010). The bacterium was also detected in B. trigonica, B. tremblayi, B. nigricornis and Bactericera sp.…”
Section: Introductionmentioning
confidence: 91%
“…Haplotype A has been found from Central to North America and New Zealand, haplotype B has been found in Mexico and the United States of America, haplotype C is present in Finland, Sweden and Norway, 2 detected in eggs, different nymph instars stages and adults of B. cockerelli (Hansen et al, 2008). The bacterium was also detected by conventional PCR in field-collected and laboratory-reared T. apicalis in southern Finland (Munyaneza et al, 2010b). Squash real-time PCR is a useful tool for the detection of nucleic acid targets in insect vectors and was successfully used to detect 'Ca.…”
Section: Introductionmentioning
confidence: 92%
“…Bactericera cockerelli Sulc is the vector of haplotypes A and B in solanaceous crops (Nelson et al, 2011). Trioza apicalis Förster was first described in carrot in Finland (Munyaneza et al, 2010b) transmitting the haplotype C (Nelson et al, 2011) and B. trigonica Hodkinson is associated with the transmission of 'Ca. L solanacearum' haplotype D in carrot and likely with haplotype E in carrot and celery in Spain (Alfaro-Fernández et al, 2012b;Nelson et al, 2012;Teresani et al, 2014).…”
Section: Hosts and Monitoring Sitesmentioning
confidence: 99%
“…Later Nissinen et al (2012) found changes in the quality of the roots by attacked plants. The possible participation of Liberibacter on this reduction was discussed by Munyaneza et al (2010). Nissinen et al (2008) performed laboratory studies on plants preferences in connection with phototaxis.…”
mentioning
confidence: 99%